The influence of the use of instructional media and interest in the learning outcomes of the pack and the manners of fifth grade elementary school students - Roberth Japeky; Yowelna Tarumasely; Rukhama Aralaha (PPPM STKIP PGRI Lamongan, 2022)
This research was conducted with the aim of knowing the effect of the use of instructional media and interest in the learning outcomes of PAK and the characteristics of fifth grade elementary school students. This study has three research objectives, namely: 1) is there an effect of the use of learning media on the learning outcomes of PAK and Budi Pekerti, 2) is there an effect of asking for the level of learning on the learning outcomes of PAK and Budi Pekerti, and 3) there is an interaction between the use of learning media and interest in learning about the results of learning PAK and Budi Pekerti. The research method used is the experimental method, with a 2x2 factorial. The research sample consisted of 41 students who were located in 2 schools, namely Letwurung Christian Elementary School. The results of the study show that: 1) there is an effect of the use of instructional media on the learning outcomes of PAK and Budi Pekerti. 2) There is an influence of interest in learning on the learning outcomes of PAK and Budi Pekerti and 3) there is an interaction between the use of learning media and interest in learning on the learning outcomes of PAK and Character. Likewise the use of instructional media and learning interests affect the learning outcomes of PAK and Characteristics of fifth-grade elementary school students.